﻿Dispersal rate of Potamophylax cingulatus and Micropterna sequax (Trichoptera) in Iceland - Gíslason,Gísli Már; Ólafsson,Erling; Alfredsson,Matthias S. (Contributions to Entomology, 2023)
During the 20th and 21st century, two species of Trichoptera have colonised Iceland. One species is Potamophylax cingulatus and the other is Micropterna sequax. Potamophylax cingulatus was not found in several extensive surveys before 1942, conducted by several entomologists. During a survey in streams in 1974–1978, the species was found to be common in east and north-east Iceland, but the Trichoptera species Apatania zonella was absent, where it was common before 1942. Searching collections of unidentified Trichoptera, a single specimen was found in east Iceland on 30 July 1959. The survey was repeated in 2004–2006 and the species had colonised most streams and rivers in Iceland and A. zonella had disappeared from many of them. Potamophylax cingulatus was first recorded in two light traps in south Iceland in 1997 with two specimens. The catch has increased continuously to 267 in 2022. Micropterna sequax was found in a single light trap at Mógilsá near Reykjavik in 2008. The annual catch has since grown from two specimens to 144. The species was found at Hvanneyri, 40 km north of the original site it was recorded from in 2018 (8 specimens) and, in 2021, it was found in Kjós, 11 km from the original site (one specimen based on a photograph). The dispersal rate for P. cingulatus was about 7–9 km/year, but the dispersal rate for the more recent settler M. sequax was found to be 4 km/year.